2021
DOI: 10.1111/aec.13101
|View full text |Cite
|
Sign up to set email alerts
|

Host plant choice and effect of temperature on feeding behaviour of Perzelia arda (Lepidoptera: Depressariidae), a leaf‐tying larva, on Nothofagaceae from the Andean Patagonian forest

Abstract: Environmental temperature may cause changes in the physiology and feeding behaviour of herbivorous insects and, consequently, in the damage they can cause. In the Andean Patagonian forest, an eco-region dominated by trees of the Nothofagaceae family, it is common to find the leaf-tying larvae Perzelia arda consuming seeds and leaves of several species of Nothofagus genus. The pattern of damage caused by P. arda in these forests varies from year to year and even within seasons. We hypothesise that this phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 44 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…These results agree with a previous study (Pietrantuono et al, 2017), which evaluated the preferences in P. arda between the leaves of several individuals of the closely related hosts N. obliqua and N. alpina, and showed that individual characteristics of each host plant (such as cellulose content) rather than taxonomic classification may determine herbivores choices. A preference gradient composed of individuals of both tree species was observed; that is, there is not one species more preferred than another but rather individual genotypes (see also Capobianco et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…These results agree with a previous study (Pietrantuono et al, 2017), which evaluated the preferences in P. arda between the leaves of several individuals of the closely related hosts N. obliqua and N. alpina, and showed that individual characteristics of each host plant (such as cellulose content) rather than taxonomic classification may determine herbivores choices. A preference gradient composed of individuals of both tree species was observed; that is, there is not one species more preferred than another but rather individual genotypes (see also Capobianco et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The data were analysed following the same methodology of Pietrantuono et al (2017) and Capobianco et al (2021). We evaluated the decisions made by the insects and established a scale of preferences based on the food choice of the larvae for each experiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations